Kajian Penerimaan Konsumen terhadap Produk “Koteja” Kopi dengan Tambahan Bahan Berkhasiat - Kurnia Harlina Dewi; Helmiyetti Helmiyetti; Nusril Nusril; Yessy Rosalina; Ronni Armando Siahaan (Jurnal Teknologi dan Industri Pertanian Indonesia, 2014)
This study aimed to asses effect of different efficacious materials and types of sugar on consumer acceptance of “Koteja” (coffee with addition of sea cucumber and ginger) based on organoleptic tests (taste, aroma, and color) and to determine the most preferred coffee by consumers and in accordance with SNI. This study was conducted by using randomized completely design with 2 (two) factors; efficacious materials (Morinda citrifolia, Piper retrofractum, Syzgium aromaticum and material mix) and types of sugar (white sugar and brown sugar). Experimental data were subjected to ANOVA test followed by DMRT with 5% level of significant. The result showed that the use of Java chili (Piper retrofractum) and brown sugar was the most preferred by consumer.